MENELAAH PESERTA DIDIK MELALUI LENSA FILSAFAT PENDIDIKAN ISLAM: PEMAHAMAN DAN IMPLEMENTASINYA - Damanhuri, Damanhuri; Barizi, Ahmad; Ardiyansyah, Ahmad (LPPM STAI DARUSSALAM LAMPUNG, 2025)
Abstract: Learners hold a central position in the educational process and, from the perspective of Islamic educational philosophy, are viewed as active subjects who must be guided according to their innate nature (fitrah). Islamic education aims to develop the learner’s full potential—physically, intellectually, and spiritually—toward the ideal of the insan kamil (perfect human). This study aims to analyze the essence, characteristics, rights and responsibilities, and ethical code of learners within the framework of Islamic educational philosophy, along with its implications in educational practice. The research employs a literature review method by examining books, scholarly articles, and other relevant academic sources. The findings indicate that learners are not merely passive recipients of knowledge, but active participants who are expected to maintain proper conduct, sincere intention, and dedication in their pursuit of learning. A comprehensive understanding of learners’ characteristics and needs enables the implementation of Islamic education to be more effective and holistic, aligning with the core values of Islam. Keywords: Learner, Islamic Educational Philosophy, Insan Kamil, Holistic Education, Learning Ethics